Synthesis of cis-Dithiocyanato bis(4,4´-Dicarboxylic acid-2,2´-bipyridine)ruthenium and its Application in Dye-Senstized Solar Cells - WANG, SONG; HONG WU , XIAO; HUA JIANG, ZHAO (Asian Journal of Chemistry, 2010)
cis-Dithiocyanato bis(4,4'-dicarboxylic acid-2,2'-bipyridine) ruthenium was synthesized from 4-methylpyridine by the reactions of cross-coupling, oxidation, conjugating reaction and ligand substitution reaction. The product and its intermediates were characterized with IR spectrum, GC-MS, NMR and elemental analysis. TiO2 films were obtained by sol-gel method and these films were sensitized by cis-RuL2(SCN)2 (L = cis-2,2'-bipyridine-4,4'-dicarboxlic acid). UV and IR absorption spectroscopy of the sensitized film indicated that the cis-RuL2(SCN)2 has attached to the surface of the TiO2 particles. In addition, cis-RuL2(SCN)2·2H2O applications in dye-sensitized solar cells were demonstrated. From the I-V curves, the open-circuit voltage (VOC) and short-circuit current (ISC) were also measured.